"IIb or not IIb" – The necessity of dissection in patients with oral squamous cell carcinoma. Issue 10 (October 2016) - Bartella, Alexander K.; Kloss-Brandstätter, Anita; Kamal, Mohammad; Teichmann, Jan; Modabber, Ali; Hölzle, Frank; Lethaus, Bernd
Abstract: The necessary extent of cervical dissection in oral squamous cell carcinoma (OSCC) is still under discussion. Due to its anatomical properties Robins level IIb has a special role in neck dissection. This study focuses on the lymph node metastatic behaviour of OSCC in level IIb and evaluates its worth of dissection. 183 consecutive patients with OSCC were retrospectively screened for age, gender, TNM classification, cancer stage (after UICC), tumour localization, tumour infiltrations depth, and affected cervical lymph node levels. Associations between lymph node metastases and the above-mentioned characteristics were evaluated using Pearson's chi square test and Spearman's rho correlation analyses. Metastases in level IIb were seen in only 3.3% of all patients, and none of these metastases were an exclusive metastasis. Lymph node metastases most likely occurred in levels I and IIa at ipsilateral sites, and metastases were significantly related to tumour size (p < 0.01) and the infiltration of lymph vessels (p < 0.001). The locations of primary cancer sites in metastatic disease were the soft palate, alveolar crest of the lower jaw and buccal mucosa. Lymph node metastases of OSCC in level IIb remain rare, especially as exclusive metastases and in clinically N-negative necks. The findings of our study support the hypothesis of sparing neck dissection in level IIb in cases of clinically negative necks.